FEATURES OF OLIGOPOLY AND ITS IMPACT ON THE COUNTRY'S ECONOMY: https://doi.org/10.5281/zenodo.13968981 - Bozorboyev, Diyorbek (Science technology&Digital finance, 2024)
In the economic literature, four forms of competition within the same network are highlighted separately. They are free competition, monopolistic competition, monopoly and oligopoly. This article deals with oligopoly, the dominant situation in determining the price and volume of production of several large producers or sellers in the network. At the same time, the specifics of oligopoly, the influence of mamlalakat in the economy and the like were analyzed.